2015
DOI: 10.4049/jimmunol.1500431
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitizer and Light Pave the Way for Cytosolic Targeting and Generation of Cytosolic CD8 T Cells Using PLGA Vaccine Particles

Abstract: The generation of CTLs is crucial in the immunological fight against cancer and many infectious diseases. To achieve this, vaccine Ags need to be targeted to the cytosol of dendritic cells, which can activate CD8 T cells via MHC class I (MHCI). Therefore, such targeting has become one of the major objectives of vaccine research. In this study, we aimed to bypass the unwanted and default MHC class II Ag presentation and trigger MHCI presentation by using a photosensitizer that, upon light activation, would faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 62 publications
(63 reference statements)
1
11
1
Order By: Relevance
“…Our results clearly showed that PCI technology could effectively induce and significantly enhance antigen-specific CD8+ CTL responses to both peptide antigens. In earlier studies, a similar effect has been demonstrated with the ovalbumin protein antigen in mice adoptively transferred with OVA 257–264 -specific transgenic T cells ( 21 23 , 50 , 51 ). However, the results in the present work are the first demonstration of priming of CD8+ T cells from the endogenous T cell pool with clinically relevant peptide sequences, moving the technology substantially closer to a clinical use for peptide vaccination in humans.…”
Section: Discussionsupporting
confidence: 69%
“…Our results clearly showed that PCI technology could effectively induce and significantly enhance antigen-specific CD8+ CTL responses to both peptide antigens. In earlier studies, a similar effect has been demonstrated with the ovalbumin protein antigen in mice adoptively transferred with OVA 257–264 -specific transgenic T cells ( 21 23 , 50 , 51 ). However, the results in the present work are the first demonstration of priming of CD8+ T cells from the endogenous T cell pool with clinically relevant peptide sequences, moving the technology substantially closer to a clinical use for peptide vaccination in humans.…”
Section: Discussionsupporting
confidence: 69%
“…As some tumor cells, e.g., ovarian cancer or lung adenocarcinoma, express folate receptors on their surface, folic acid was applied to facilitate delivery of chemotherapeutic agents [17] in patients with platinum-refractory epithelial ovarian, primary peritoneal, or endometrial cancer [18] and progressive lung adenocarcinoma [19]. Other pharmaceutical strategies for cytosolic targeting of drugs include cationic particles to shuffle antigens across the negatively charged cellular membrane [20,21], pH-sensitive and fusogenic liposomes that break up acidified phagolysosomes [22,23], and micelle-based immune-stimulating complexes (ISCOMs) that may facilitate antigen cross-presentation [22,24]. Very recently, reports on the use of photochemical internalization (PCI), which is a further development of PDT, has been suggested as a method to internalize cytotoxic therapeutics in tumor cells [25][26][27][28][29][30][31][32] or vaccine antigens in antigen-presenting cells (APC) [20,22,[33][34][35][36][37].…”
Section: Methods For Cytosolic Targetingmentioning
confidence: 99%
“…Bruno et al demonstrated that PCI-based vaccination could be performed with antigen and photosensitizer contained in a particulate antigen delivery system composed of poly(lactide-co-glycolide) (PLGA) microparticles of approximately 1 µm in size [22]. Mice immunized with particles containing OVA and TPCS2a showed stronger CD8 T-cell proliferation than mice immunized with PLGA particles containing OVA antigen without TPCS2a.…”
Section: Pci Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…In order to promote an immune response resulting in the priming of cytotoxic T‐lymphocytes, antigens need to be delivered in the cytoplasm of dendritic cells, thereby Bruno et al developed PLGA microparticles loaded with OVA and functionalized with tetraphenyl chlorine disulphonate as a photosensitizer to trigger the release of the antigen in the cytosolic compartment. The immunization with these particles induced the production of CD8 T‐lymphocytes and the prevention of tumor growth …”
Section: Plga Particlesmentioning
confidence: 99%